Noise jamming of a FM band commensal sensor. Issue 6 (5th June 2017) - Inggs, Michael; Tong, Craig; O'Hagan, Daniel; Böniger, Urs; Siegenthaler, Urs; Schüpbach, Christof; Pratisto, Hans
Abstract : We define commensal sensors (CSs) as a class of EM sensor that use the emissions of other systems to fulfil their sensing function, without having any impact or collaboration with the emitter of opportunity. The jamming of CS systems, and possible Electronic Protection (EP) responses to such jamming have not received more than a passing reference in the open literature. The authors examine a specific case of a sensor exploiting FM Band transmissions, with a multi‐receiver configuration (single transmit site, many spatially distributed receivers) and find that although modest jammer power can be very effective in jamming a single node of the CS, the unknown geometry and frequencies of operation of the CS will make it difficult to jam in practice. Simple null steering by the CS receivers is very effective. The authors also note that the CS sensor system requires excellent electronic support (ES) to be aware of electronic attack. The study reviews the tactical situation, and the very sparse literature. This is followed by some analysis of the effect of noise jamming, followed by simulations of jamming, with and without receiver null steering, as well as some self‐protection jamming.